Agricultural Productivity Strategies for the Future: Addressing U.S. and Global Challenges - Buchanan, Gale; Herdt, Robert W.; Tweeten, Luther G.; Borlaug, Norman E. (Council for Agricultural Science and Technology (CAST), 2010)
This timely Issue Paper (IP 45) includes a preface from Dr. Norman E. Borlaug and has been prepared as an update of CAST Paper No. 1, written by Dr. Borlaug in 1973. The authors of the current paper address (1) future demands facing agriculture; (2) the relationship of bioenergy and bioproducts to agriculture; (3) major issues impacting future U.S. agricultural productivity; (4) major issues facing agricultural productivity in other parts of the world; (5) strategies to meet future food needs; and (6) examples of research areas that could enable the next “Green Revolution.” The authors question the commitment by the United States and many other countries for support of agricultural research and indicate the far-reaching impact that such research, education, and resulting technology–or lack thereof–will have on the nation and the world.